2012
DOI: 10.1002/jmri.23891
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxygenation level‐dependent (BOLD) contrast magnetic resonance imaging (MRI) for prediction of breast cancer chemotherapy response: A pilot study

Abstract: We have successfully implemented an oxygen-breathing challenge BOLD contrast technique as part of the standard breast MRI exam in patients with locally advanced breast cancer. The preliminary observation that a large BOLD response correlated with better treatment response suggests a predictive capability for BOLD MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 44 publications
1
52
0
1
Order By: Relevance
“…Since then, BOLD MR imaging methods have been widely used in preclinical and clinical studies, particularly to measure functional activity in the brain (12,13). BOLD contrast methods also have been used to assess the pathophysiology of tumors and to monitor tumor response to therapy (14)(15)(16). Preclinical and clinical studies have shown the utility of BOLD MR imaging in assessment of the hemodynamic response of tumors during hyperoxia (carbogen: 95% O 2 , 5% CO 2 ) and hypercapnia (95% room air, 5% CO 2 ) challenges (17)(18)(19)(20).…”
Section: Implications For Patient Carementioning
confidence: 99%
“…Since then, BOLD MR imaging methods have been widely used in preclinical and clinical studies, particularly to measure functional activity in the brain (12,13). BOLD contrast methods also have been used to assess the pathophysiology of tumors and to monitor tumor response to therapy (14)(15)(16). Preclinical and clinical studies have shown the utility of BOLD MR imaging in assessment of the hemodynamic response of tumors during hyperoxia (carbogen: 95% O 2 , 5% CO 2 ) and hypercapnia (95% room air, 5% CO 2 ) challenges (17)(18)(19)(20).…”
Section: Implications For Patient Carementioning
confidence: 99%
“…This discrepancy is thought to relate to differences in tumor biology across histologies 15, 21, 22. Such discordant results may be explained by T2*‐weighted signal dependence on physiological factors, including the hematocrit, blood volume (BV), vessel caliber,23, 24 and the intermittent tumor vessel blood flow 16, 25.…”
mentioning
confidence: 99%
“…In DWI advanced techniques such as intravoxel incoherent motion, stretched exponential DWI, and DW kurtosis imaging are being investigated and hold promise for providing additional robust imaging biomarkers that can be incorporated in radiogenomic studies [30]. In addition, other MRI techniques that may be used for radiogenomic research include spectroscopy (proton, phosphorus, lipid), sodium imaging [50], CEST imaging [24], BOLD [21], and arterial spin labeling MRI [43]. Radiogenomics research in BC is still in its infancy.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%